The Cantor Set as an Inverse Limit of Upper Semicontinuous Functions That Are the Union of Mappings - Capul´ın, F; Ruiz del Portal, F R; Sánchez-Garrido, M (Topology Proceedings, 2021)
In this paper, we study the generalized inverse limit with a single upper semi-continuous function F such that it is the union of mappings from a continuum X into itself. Using the concept of Dom(F), we show that if X has the fixed point property or X is an absolute neighbourhood retract (ANR) space and Dom(F) is a non-degenerate finite set, the generalized inverse limit is homeomorphic to the Cantor set.